Volume 7: Fluids Engineering 2017
DOI: 10.1115/imece2017-71512
|View full text |Cite
|
Sign up to set email alerts
|

A Leak Localization Model for Gas-Liquid Two-Phase Flows in Nearly Horizontal Pipelines

Abstract: In the oil industry the localization of a leak that occurs in a pipeline is an important piece of information that needs to be obtained before mitigating actions can be taken to remedy the leak effects. In this paper we are particularly interested in testing a leak localization model for two-phase flows based upon the intersection of the hydraulic grade lines emanating from the pipeline ends. This methodology is commonly applied to single-phase-flows. In two-phase flows, the flow-pattern that develops along th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The pressure distribution proved effective and scientific to characterise stratified flow behaviours in this study. The effect of leak on stratified flow behaviours induced by leaks has previously observed similar to the monophase pipeline leakage in the previous study (Figueiredo et al 2017). They concluded that the leak localisation strategy based on the upstream and downstream pressure profiles commonly employed in monophase flow pipeline leakage could be extended to the stratified-flow system.…”
Section: Pipeline Leaks Comparison Against Experimental Datasupporting
confidence: 64%
See 2 more Smart Citations
“…The pressure distribution proved effective and scientific to characterise stratified flow behaviours in this study. The effect of leak on stratified flow behaviours induced by leaks has previously observed similar to the monophase pipeline leakage in the previous study (Figueiredo et al 2017). They concluded that the leak localisation strategy based on the upstream and downstream pressure profiles commonly employed in monophase flow pipeline leakage could be extended to the stratified-flow system.…”
Section: Pipeline Leaks Comparison Against Experimental Datasupporting
confidence: 64%
“…However, this study was only limited to a 1-D pipeline, assuming that the pipeline was made up of a series of small segments in which each node along the pipe modelled the local flow characteristics. A similar study presented by Figueiredo et al (2017) investigated the effect of leakage on two-phase flow behaviour in nearly horizontal pipelines. In their study, the impact of longitudinal leak location on stratified flows was investigated.…”
Section: Related Workmentioning
confidence: 96%
See 1 more Smart Citation
“…For example, Kam 105 used a single-dimensional pipeline made up of small networks, wherein one network was used to model flow behavior. In other work, Figuerido et al 106 investigated the dual-phase flow impact of the behavior of leaks in horizontally oriented networks and considered longitudinal leak localization in stratified flows. Figuerido et al 106 determined that stratified flow systems could adopt typical pressure profiles utilized in monophase leaks.…”
Section: Effectiveness Of Ldms and Llms Against Possible Leakagementioning
confidence: 99%
“…In other work, Figuerido et al 106 investigated the dual-phase flow impact of the behavior of leaks in horizontally oriented networks and considered longitudinal leak localization in stratified flows. Figuerido et al 106 determined that stratified flow systems could adopt typical pressure profiles utilized in monophase leaks. However, similar to other studies, this research simulated single-dimensional pipelines, which are inadequate for gaining a holistic comprehension of the dynamic nature of multiphase flow networks.…”
Section: Effectiveness Of Ldms and Llms Against Possible Leakagementioning
confidence: 99%